Crack Healing in Ti2Al0.5Sn0.5C–Al2O3 Composites. Issue 5 (13th February 2015) - Bei, Guo Ping; Pedimonte, Birgit Joana; Pezoldt, Marc; Ast, Johannes; Fey, Tobias; Goeken, Mathias; Greil, Peter
Abstract : Oxidation induced crack healing of Al2 O3 composites loaded with a MAX phase based repair filler (Ti2 Al0.5 Sn0.5 C) was examined. The fracture strength of 20 vol% repair filler loaded composites containing artificial indent cracks recovered fully to the level of the virgin material upon isothermal annealing in air atmosphere after 48 h at 700°C and 0.5 h at 900°C. SEM‐EBSD analysis of crack microstructure indicates two different oxidation reaction regimes to govern the crack filling: near the surface SnO2, TiO2, and Al2 O3 were formed whereas deeply inside the cracks Al2 O3 and TiO2 and metallic Sn were detected. The presence of elemental Sn was attributed to partial oxidation of aluminum and titanium which lowered the local oxygen concentration below a threshold value required for Sn oxidation to SnO2 . Thus, Ti2 Al0.5 Sn0.5 C may represent an efficient repair filler system to trigger oxidation induced crack healing in ceramic composites at temperatures below 1000°C.